2006
DOI: 10.1007/s00709-006-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and germination of Vitis vinifera cv. Loureiro pollen

Abstract: The cultivar Loureiro of Vitis vinifera is one of the most economically important, recommended in almost the totality of the Região Demarcada dos Vinhos Verdes. In vineyards, the grape productivity of this cultivar is normal while in others it is extremely low. The aim of this work was to study the morphology and germination of Vitis vinifera cv. Loureiro pollen with high and low productivity. The pollen grain was examined under light, transmission and scanning electron microscopy. Typically V. vinifera pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…The results showed that pollen stored at -80°C maintains a good germination during the same season. Abreu et al (2006) investigated the causes of low productivity of V. vinifera cv. 'Loureiro' pollen by studding pollen viability using fluorochromatic reaction and pollen germination ability by in vitro assays and reported that the acolporated pollen grains of mentioned cultivar are viable, but no germination was recorded.…”
Section: Analysis Of Variances Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that pollen stored at -80°C maintains a good germination during the same season. Abreu et al (2006) investigated the causes of low productivity of V. vinifera cv. 'Loureiro' pollen by studding pollen viability using fluorochromatic reaction and pollen germination ability by in vitro assays and reported that the acolporated pollen grains of mentioned cultivar are viable, but no germination was recorded.…”
Section: Analysis Of Variances Inmentioning
confidence: 99%
“…Pollen viability levels, environmental conditions, and compatibility among cultivars are important for the normal fruit set in all of the fruit trees and grapes (Dantas et al, 2005;Kelen and Demitas, 2003). Different nutrition conditions and germination methods for many plant species and varieties were used by researchers (Abreu et al, 2006;Kelen and Demitas, 2003). Carreño et al (2010) studied the influence of some compounds and temperature on pollen germination capability in some table grape cultivars and reported that optimum temperature for pollen germination depend on the genotype, but in general ranged 25 to 30°C.…”
Section: Introductionmentioning
confidence: 99%
“…1G and H). In V. vinifera and Vitis lubruscana pollen, both acolporated and tricolporated pollen stain as viable, but only tricolporated pollen is able to germinate (Abreu et al, 2006;Ahmedullah, 1983). As in muscadine, cultivars only producing acolporated pollen have reflexed stamens ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tricolporated pollen have plastids filled with numerous starch granules, whereas the plastids in acolporated pollen lack starch grains. Additionally, acolporated pollen plasma membranes presented an irregular shape and in some regions detached from the pollen wall (Abreu et al, 2006). Pollen grains may also differ in size, shape, and exine characteristics that can be used as parameters in cultivar identification of grapes.…”
Section: Resultsmentioning
confidence: 99%
“…There is a big variation in optimum germination conditions of pollen among plant species and cultivars (Kelen and Demirtas 2003). Many researchers have been performed to determine quantitatively and qualitatively the components necessary for the best composition of culture medium in pollen grain germination for different species pollens (Abreu, et al 2006;Dane, et al 2004;Eti 1991;Eti, et al 1998;Kelen and Demirtas 2003;Liu and Zhu 1985;Sharafi 2011).…”
Section: Introductionmentioning
confidence: 99%